(* Title: HOL/Library/Stirling.thy
Author: Amine Chaieb
Author: Florian Haftmann
Author: Lukas Bulwahn
Author: Manuel Eberl
*)
section \Stirling numbers of first and second kind\
theory Stirling
imports Main
begin
subsection \Stirling numbers of the second kind\
fun Stirling :: "nat \ nat \ nat"
where
"Stirling 0 0 = 1"
| "Stirling 0 (Suc k) = 0"
| "Stirling (Suc n) 0 = 0"
| "Stirling (Suc n) (Suc k) = Suc k * Stirling n (Suc k) + Stirling n k"
lemma Stirling_1 [simp]: "Stirling (Suc n) (Suc 0) = 1"
by (induct n) simp_all
lemma Stirling_less [simp]: "n < k \ Stirling n k = 0"
by (induct n k rule: Stirling.induct) simp_all
lemma Stirling_same [simp]: "Stirling n n = 1"
by (induct n) simp_all
lemma Stirling_2_2: "Stirling (Suc (Suc n)) (Suc (Suc 0)) = 2 ^ Suc n - 1"
proof (induct n)
case 0
then show ?case by simp
next
case (Suc n)
have "Stirling (Suc (Suc (Suc n))) (Suc (Suc 0)) =
2 * Stirling (Suc (Suc n)) (Suc (Suc 0)) + Stirling (Suc (Suc n)) (Suc 0)"
by simp
also have "\ = 2 * (2 ^ Suc n - 1) + 1"
by (simp only: Suc Stirling_1)
also have "\ = 2 ^ Suc (Suc n) - 1"
proof -
have "(2::nat) ^ Suc n - 1 > 0"
by (induct n) simp_all
then have "2 * ((2::nat) ^ Suc n - 1) > 0"
by simp
then have "2 \ 2 * ((2::nat) ^ Suc n)"
by simp
with add_diff_assoc2 [of 2 "2 * 2 ^ Suc n" 1]
have "2 * 2 ^ Suc n - 2 + (1::nat) = 2 * 2 ^ Suc n + 1 - 2" .
then show ?thesis
by (simp add: nat_distrib)
qed
finally show ?case by simp
qed
lemma Stirling_2: "Stirling (Suc n) (Suc (Suc 0)) = 2 ^ n - 1"
using Stirling_2_2 by (cases n) simp_all
subsection \Stirling numbers of the first kind\
fun stirling :: "nat \ nat \ nat"
where
"stirling 0 0 = 1"
| "stirling 0 (Suc k) = 0"
| "stirling (Suc n) 0 = 0"
| "stirling (Suc n) (Suc k) = n * stirling n (Suc k) + stirling n k"
lemma stirling_0 [simp]: "n > 0 \ stirling n 0 = 0"
by (cases n) simp_all
lemma stirling_less [simp]: "n < k \ stirling n k = 0"
by (induct n k rule: stirling.induct) simp_all
lemma stirling_same [simp]: "stirling n n = 1"
by (induct n) simp_all
lemma stirling_Suc_n_1: "stirling (Suc n) (Suc 0) = fact n"
by (induct n) auto
lemma stirling_Suc_n_n: "stirling (Suc n) n = Suc n choose 2"
by (induct n) (auto simp add: numerals(2))
lemma stirling_Suc_n_2:
assumes "n \ Suc 0"
shows "stirling (Suc n) 2 = (\k=1..n. fact n div k)"
using assms
proof (induct n)
case 0
then show ?case by simp
next
case (Suc n)
show ?case
proof (cases n)
case 0
then show ?thesis
by (simp add: numerals(2))
next
case Suc
then have geq1: "Suc 0 \ n"
by simp
have "stirling (Suc (Suc n)) 2 = Suc n * stirling (Suc n) 2 + stirling (Suc n) (Suc 0)"
by (simp only: stirling.simps(4)[of "Suc n"] numerals(2))
also have "\ = Suc n * (\k=1..n. fact n div k) + fact n"
using Suc.hyps[OF geq1]
by (simp only: stirling_Suc_n_1 of_nat_fact of_nat_add of_nat_mult)
also have "\ = Suc n * (\k=1..n. fact n div k) + Suc n * fact n div Suc n"
by (metis nat.distinct(1) nonzero_mult_div_cancel_left)
also have "\ = (\k=1..n. fact (Suc n) div k) + fact (Suc n) div Suc n"
by (simp add: sum_distrib_left div_mult_swap dvd_fact)
also have "\ = (\k=1..Suc n. fact (Suc n) div k)"
by simp
finally show ?thesis .
qed
qed
lemma of_nat_stirling_Suc_n_2:
assumes "n \ Suc 0"
shows "(of_nat (stirling (Suc n) 2)::'a::field_char_0) = fact n * (\k=1..n. (1 / of_nat k))"
using assms
proof (induct n)
case 0
then show ?case by simp
next
case (Suc n)
show ?case
proof (cases n)
case 0
then show ?thesis
by (auto simp add: numerals(2))
next
case Suc
then have geq1: "Suc 0 \ n"
by simp
have "(of_nat (stirling (Suc (Suc n)) 2)::'a) =
of_nat (Suc n * stirling (Suc n) 2 + stirling (Suc n) (Suc 0))"
by (simp only: stirling.simps(4)[of "Suc n"] numerals(2))
also have "\ = of_nat (Suc n) * (fact n * (\k = 1..n. 1 / of_nat k)) + fact n"
using Suc.hyps[OF geq1]
by (simp only: stirling_Suc_n_1 of_nat_fact of_nat_add of_nat_mult)
also have "\ = fact (Suc n) * (\k = 1..n. 1 / of_nat k) + fact (Suc n) * (1 / of_nat (Suc n))"
using of_nat_neq_0 by auto
also have "\ = fact (Suc n) * (\k = 1..Suc n. 1 / of_nat k)"
by (simp add: distrib_left)
finally show ?thesis .
qed
qed
lemma sum_stirling: "(\k\n. stirling n k) = fact n"
proof (induct n)
case 0
then show ?case by simp
next
case (Suc n)
have "(\k\Suc n. stirling (Suc n) k) = stirling (Suc n) 0 + (\k\n. stirling (Suc n) (Suc k))"
by (simp only: sum_atMost_Suc_shift)
also have "\ = (\k\n. stirling (Suc n) (Suc k))"
by simp
also have "\ = (\k\n. n * stirling n (Suc k) + stirling n k)"
by simp
also have "\ = n * (\k\n. stirling n (Suc k)) + (\k\n. stirling n k)"
by (simp add: sum.distrib sum_distrib_left)
also have "\ = n * fact n + fact n"
proof -
have "n * (\k\n. stirling n (Suc k)) = n * ((\k\Suc n. stirling n k) - stirling n 0)"
by (metis add_diff_cancel_left' sum_atMost_Suc_shift)
also have "\ = n * (\k\n. stirling n k)"
by (cases n) simp_all
also have "\ = n * fact n"
using Suc.hyps by simp
finally have "n * (\k\n. stirling n (Suc k)) = n * fact n" .
moreover have "(\k\n. stirling n k) = fact n"
using Suc.hyps .
ultimately show ?thesis by simp
qed
also have "\ = fact (Suc n)" by simp
finally show ?case .
qed
lemma stirling_pochhammer:
"(\k\n. of_nat (stirling n k) * x ^ k) = (pochhammer x n :: 'a::comm_semiring_1)"
proof (induct n)
case 0
then show ?case by simp
next
case (Suc n)
have "of_nat (n * stirling n 0) = (0 :: 'a)" by (cases n) simp_all
then have "(\k\Suc n. of_nat (stirling (Suc n) k) * x ^ k) =
(of_nat (n * stirling n 0) * x ^ 0 +
(\i\n. of_nat (n * stirling n (Suc i)) * (x ^ Suc i))) +
(\i\n. of_nat (stirling n i) * (x ^ Suc i))"
by (subst sum_atMost_Suc_shift) (simp add: sum.distrib ring_distribs)
also have "\ = pochhammer x (Suc n)"
by (subst sum_atMost_Suc_shift [symmetric])
(simp add: algebra_simps sum.distrib sum_distrib_left pochhammer_Suc flip: Suc)
finally show ?case .
qed
text \A row of the Stirling number triangle\
definition stirling_row :: "nat \ nat list"
where "stirling_row n = [stirling n k. k \ [0.. n \ stirling_row n ! k = stirling n k"
by (simp add: stirling_row_def del: upt_Suc)
lemma length_stirling_row [simp]: "length (stirling_row n) = Suc n"
by (simp add: stirling_row_def)
lemma stirling_row_nonempty [simp]: "stirling_row n \ []"
using length_stirling_row[of n] by (auto simp del: length_stirling_row)
(* TODO Move *)
lemma list_ext:
assumes "length xs = length ys"
assumes "\i. i < length xs \ xs ! i = ys ! i"
shows "xs = ys"
using assms
proof (induction rule: list_induct2)
case Nil
then show ?case by simp
next
case (Cons x xs y ys)
from Cons.prems[of 0] have "x = y"
by simp
moreover from Cons.prems[of "Suc i" for i] have "xs = ys"
by (intro Cons.IH) simp
ultimately show ?case by simp
qed
subsubsection \Efficient code\
text \
Naively using the defining equations of the Stirling numbers of the first
kind to compute them leads to exponential run time due to repeated
computations. We can use memoisation to compute them row by row without
repeating computations, at the cost of computing a few unneeded values.
As a bonus, this is very efficient for applications where an entire row of
Stirling numbers is needed.
\
definition zip_with_prev :: "('a \ 'a \ 'b) \ 'a \ 'a list \ 'b list"
where "zip_with_prev f x xs = map2 f (x # xs) xs"
lemma zip_with_prev_altdef:
"zip_with_prev f x xs =
(if xs = [] then [] else f x (hd xs) # [f (xs!i) (xs!(i+1)). i \ [0..i. f (xs ! i) (xs ! (i + 1))) [0..a b. a + n * b) y xs @ [1]"
by (induct xs arbitrary: y) (simp_all add: zip_with_prev_def)
lemma stirling_row_code [code]:
"stirling_row 0 = [1]"
"stirling_row (Suc n) = stirling_row_aux n 0 (stirling_row n)"
proof goal_cases
case 1
show ?case by (simp add: stirling_row_def)
next
case 2
have "stirling_row (Suc n) =
0 # [stirling_row n ! i + stirling_row n ! (i+1) * n. i \ [0.. Suc n"
by simp
then consider "i = 0 \ i = Suc n" | "i > 0" "i \ n"
by linarith
then show ?case
proof cases
case 1
then show ?thesis
by (auto simp: nth_stirling_row nth_append)
next
case 2
then show ?thesis
by (cases i) (simp_all add: nth_append nth_stirling_row)
qed
next
case length
then show ?case by simp
qed
also have "0 # [stirling_row n ! i + stirling_row n ! (i+1) * n. i \ [0..a b. a + n * b) 0 (stirling_row n) @ [1]"
by (cases n) (auto simp add: zip_with_prev_altdef stirling_row_def hd_map simp del: upt_Suc)
also have "\ = stirling_row_aux n 0 (stirling_row n)"
by (simp add: stirling_row_aux_correct)
finally show ?case .
qed
lemma stirling_code [code]:
"stirling n k =
(if k = 0 then (if n = 0 then 1 else 0)
else if k > n then 0
else if k = n then 1
else stirling_row n ! k)"
by (simp add: nth_stirling_row)
end